(untitled) (Rajarshi Janak University Research Journal, 2025)
Nepal is a culturally, socially, linguistically and religiously diverse country, having over hundred recognized ethnic groups. This study brings the alarming issue of highly under representation of Madheshi in Nepal Army (NA). The study explores the apathy and ignorance of NA towards recruitment of candidates from Madheshi community. As a result, the presence of Madheshi people in the Nepal Army has historically been low with respect to their population share. So, the study examines the historical patterns of exclusion of Madheshi communities from the Nepal Army. It also examines post-conflict integration efforts following the 2006 Comprehensive Peace Accord, and contemporary evidence on representation and hindrances faced by Madheshis looking for military careers. This research work uses secondary sources: academic studies, scholarly articles, government reports and data, authentic media reports, and INGO/NGO analyses and interpretations to reach to a conclusion. Descriptive method has been used for analysis and the interpretation of the data. The results of the study show that despite Madheshi’s population of 22.22%, their representation in Nepal Army stands at meagre 2.88%. The study also presents issues about the discriminatory behaviour toward Madheshis who have already been recruited in the Nepal Army. This article argues that the increasing representation from Madheshi communities in NA would ensure responsiveness and trust of the Nepal Army.